Pengaruh Return On Asset (ROA) dan Debt To Equity Ratio (DER) Terhadap Harga Saham - Bayu Ramadhan; Nursito Nursito (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
The capital market has an important role in increasing the efficiency of the financial system and is one of the vital financial intermediation institutions in the modern economy of a country. This study aims to examine the effect of ROA and DER on stock prices in automotive and component manufacturing companies listed on the Indonesia Stock Exchange for the period 2014-2019. Purposive sampling was used to collect samples from the population, obtained 5 automotive sub-sector companies and components from 13 automotive sub-sector companies and components as samples. So that the number of samples studied was 30 data counted by 6 years. The research method used is descriptive and verification quantitative research methods. Based on the results of research conducted by the author using SPSS 24 for partial and simultaneous tests, namely: ROA has no effect on stock prices, DER is significant positive on stock prices. Simultaneously ROA, DER affect stock prices. Based on the determinant coefficient test, the independent variable affects the dependent variable by 40.7% and there are still 59.3% factors from the variables outside this study. Keywords: ROA, DER, Stock Price